Osmotic stress tolerance and transcriptome analysis of Gluconobacter oxydans to extra-high titers of glucose - Liu, Xinlu; Wang, Zhiwei; Xiao, Jianjian; Zhou, Xin; Xu, Yong (Frontiers in Microbiology, 2022)
Gluconobacter oxydans has been widely acknowledged as an ideal strain for industrial bio-oxidations with fantastic yield and productivity. Even 600 g/L xylose can be catalyzed efficiently in a sealed and compressed oxygen supplying bioreactor. Therefore, the present study seeks to explore the osmotic stress tolerance against extra-high titer of representative lignocellulosic sugars like glucose. G. oxydans can well adapted and fermented with initial 600 g/L glucose, exhibiting the highest bio-tolerance in prokaryotic strains and the comparability to the eukaryotic strain of Saccharomyces cerevisiae. 1432 differentially expressed genes corresponding to osmotic pressure are detected through transcriptome analysis, involving several genes related to the probable compatible solutes (trehalose and arginine). G. oxydans obtains more energy by enhancing the substrate-level phosphorylation, resulting in the increased glucose consumption rate after fermentation adaption phase. This study will provide insights into further investigation of biological tolerance and response to extra-high titers of glucose of G. oxydans.